2002
DOI: 10.1002/yea.883
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Saccharomyces cerevisiae Sco2p reveals a high degree of redundancy with Sco1p

Abstract: The Saccharomyces cerevisiae gene SCO1 has been shown to play an essential role in the transfer of copper to the Cu A -centre of the mitochondrial cytochrome c oxidase subunit Cox2p. By contrast, the function of Sco2p, the gene product of the highly homologous SCO2 gene, remains to be elucidated. Deletion of the SCO2 gene does not affect growth on a variety of carbon sources, including glycerol, lactate and ethanol. We report here, that Sco2p is anchored in the mitochondrial membrane by a single transmembrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 42 publications
2
24
0
2
Order By: Relevance
“…This observation suggests that the residues separating the transmembrane helix from the folded domain are essential to promote dimerization. In vivo studies also have shown that this N-terminal region is crucial for yeast Sco1 function and cannot be replaced, even by its Sco2 counterpart (20).…”
Section: Resultsmentioning
confidence: 99%
“…This observation suggests that the residues separating the transmembrane helix from the folded domain are essential to promote dimerization. In vivo studies also have shown that this N-terminal region is crucial for yeast Sco1 function and cannot be replaced, even by its Sco2 counterpart (20).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, energy-minimized homology models of hSCO2 and the R. spheroides homolog, PrrC, also indicate a predominately negative surface (data not shown). Because Lode et al (30,31) reported a stable complex between yeast Cox2p and Sco1p/Sco2p, we mapped the electrostatic potential of subunit II from bovine COX (32). Interestingly, this surface is also negatively charged (data not shown).…”
mentioning
confidence: 96%
“…More precisely, Sco2 contains "electron transport" and "bipartite nuclear localization signal" motifs in ORF0 and ORF‫,1מ‬ respectively. It is similar to Sco1p and may have a redundant function with Sco1p in delivery of copper to cytochrome c oxidase; it interacts with Cox2p (Lode et al 2002). Surprisingly, yeast two-hybrid assays also show it interacts with Cyclin-B (Ito et al 2001).…”
Section: Discussionmentioning
confidence: 99%